Water requirement estimates of feed and fodder production for Indian livestock vis a vis livestock water productivity - SINGH, SULTAN; MISHRA, A K; SINGH, J B; RAI, S K; BAIG, M J; BIRADAR, N; KUMAR, A; VERMA, O P S (The Indian Journal of Animal Sciences, 2014)
Water required for feed production accounts the major part of livestock requirement and primarily influences the livestock water productivity. Water requirement to produce a kg DM of common green fodder, protein and energy feeds varied from 267 (sorghum) to 713.3 liter (lucerne), 1,000.0 (linseed) to 2,000.0 liter (soybean) and 690.0 (maize grain) to 850.0 liter (oat grain), respectively. Total water requirement estimated for livestock population 2003 and 2010 were 16.30 and 16.15 MCM, where cattle (both indigenous and crossbred) had highest water requirement (10.11 and 9.51 MCM). To meet the green fodder and concentrate requirement of livestock 151.72, 156.83 and 161.81 and 142.76, 157.67 and 172.04 BCM water required in year 2015, 2020 and 2025, respectively. Livestock water productivity to produce 1 kg milk ranged from 475.0 to 3,751.0 liter depending on the animal rearing system (extensive to intensive system), while to produce a kg of meat water requirement ranges from 8,215.0 to 9,680.0 liter depending on the animal species. Livestock water requirement for drinking and washing is very low (3.6%) than for feed and fodder production, while the livestock water productivity varies widely with their rearing system (extensive vs. intensive system) and animal species.